Analogical simulation of salt flow and associated structures in different extensional conditions. (December 2022) - de Oliveira Santos, Carla Hemillay; Alves Da Silva, Fernando César; Pichel, Leonardo Muniz
Abstract: The salt layer thickness variability and the timing of salt deposition in relation to rifting (prerift salt, synrift salt, and late synrift/postrift salt) influence salt flow and the resulting growth, geometry, and kinematics of salt bodies under different extensional conditions. We apply analogue modelling to analyze the influence and interplay of each of these parameters through three series of experiments focusing on extensional salt tectonics. The first (Series I) simulates thick-skinned extension of a tabular salt layer in the absence of basement structures and explore the effects of variable salt thicknesses and extensional structural styles. Series II tests the degree of mechanical coupling of sub- and supra-salt faults according to contrasting salt thicknesses over a rotating rift block. Series III explores thin-skinned, gravity-driven deformation implementing models of i) pure-gliding (S1 ), ii) pure-spreading (S2 ) and iii) a combination of both (S3 ). Series I shows that the degree of symmetry and the kinematics of the structures vary due to the influence of the thickness of the salt layer. Thick salt layers tend to nucleate symmetric rifts and associated diapirs, while thin salt layers form rifts that are strongly asymmetric and rotated towards the direction of extension. Series II demonstrates that the number and dimensions of peripheral post-salt grabens, rollers, and reactive diapirs depends on the degree of coupling between sub- and supra-salt, which in turn is controlled by how the salt layer is distributed over active rift structures. Series III shows that deformation is compartmentalized into proximal, transitional, and distal domains which are characterized by extension, translation and contraction, respectively. The style and lateral extent of these domains however vary. In models where deformation is driven exclusively by tilting of the salt layer (S1 ) and open-toe salt advance, there is development of linear grabens cored by reactive-passive diapirs throughout most of the model length. This produces a more abrupt transition between the extensional and contractional domains and limited downdip salt inflation. In the pure-spreading model (S2 ), where deformation is driven solely by differential loading there is formation of a wide zone of salt inflation at the toe-of-slope and an overall greater number of contractional structures at the downdip end of the model, beyond the slope. In S3 there is development of a more variable suite of salt and overburden structures as typically observed along salt-bearing passive margins. In this model, deformation is characterized by the development of rollover and normal growth faults in the proximal domain that transition downdip onto upright diapirs associated with bowl-shaped minibasins, halokinetic sequences rotated and megaflaps. Our study improves our understanding of the extensional salt tectonic systems and the controls on different salt and post-salt geometries and kinematics. Highlights: Analogical simulations of salt tectonics under extensional conditions. Influence of salt thickness and the spreading and gliding mechanisms. Effects of modelling parameters in the resulting salt structural styles.